(a) Find the equation of a straight line passing through the point
(
−
2
,
2
)
(
−
2
,
2
)
(-2,2) (-2,2) ( − 2 , 2 ) and slope -3 .
⇒
⇒
=>quad \Rightarrow \quad ⇒ Here, passing point
(
x
1
,
y
1
)
=
(
−
2
,
2
)
x
1
,
y
1
=
(
−
2
,
2
)
(x_(1),y_(1))=(-2,2) \left(\mathrm{x}_{1}, \mathrm{y}_{1}\right)=(-2,2) ( x 1 , y 1 ) = ( − 2 , 2 )
Slope
(
m
)
=
−
3
(
m
)
=
−
3
(m)=-3 (m)=-3 ( m ) = − 3
We know that;
Equation of line in point slope form is;
y
−
y
1
=
m
(
x
−
x
1
)
or,
y
−
2
=
−
3
(
x
+
2
)
or,
y
−
2
=
−
3
x
−
6
∴
3
x
+
y
+
4
=
0
is the required equation.
y
−
y
1
=
m
x
−
x
1
or,
y
−
2
=
−
3
(
x
+
2
)
or,
y
−
2
=
−
3
x
−
6
∴
3
x
+
y
+
4
=
0
is the required equation.
{:[,y-y_(1)=m(x-x_(1))],[" or, ",y-2=-3(x+2)],[" or, ",y-2=-3x-6],[:.quad,3x+y+4=0" is the required equation. "]:} \begin{array}{ll}
& y-y_{1}=m\left(x-x_{1}\right) \\
\text { or, } & y-2=-3(x+2) \\
\text { or, } & y-2=-3 x-6 \\
\therefore \quad & 3 x+y+4=0 \text { is the required equation. }
\end{array} y − y 1 = m ( x − x 1 ) or, y − 2 = − 3 ( x + 2 ) or, y − 2 = − 3 x − 6 ∴ 3 x + y + 4 = 0 is the required equation.
(b) Find the equation of a straight line passing through the point
(
4
,
5
)
(
4
,
5
)
(4,5) (4,5) ( 4 , 5 ) and slope
=
7
=
7
=7 =7 = 7 .
⇒
⇒
=>quad \Rightarrow \quad ⇒ Here, passing point
(
x
1
,
y
1
)
=
(
4
,
5
)
x
1
,
y
1
=
(
4
,
5
)
(x_(1),y_(1))=(4,5) \left(x_{1}, y_{1}\right)=(4,5) ( x 1 , y 1 ) = ( 4 , 5 )
Slope
(
m
)
=
7
(
m
)
=
7
(m)=7 (m)=7 ( m ) = 7
We know that;
Equation of line in point slope form is;
y
−
y
1
=
m
(
x
−
x
1
)
or,
y
−
5
=
7
(
x
−
4
)
or,
y
−
5
=
7
x
−
28
∴
7
x
−
y
−
23
=
0
is the required equation.
y
−
y
1
=
m
x
−
x
1
or,
y
−
5
=
7
(
x
−
4
)
or,
y
−
5
=
7
x
−
28
∴
7
x
−
y
−
23
=
0
is the required equation.
{:[,y-y_(1)=m(x-x_(1))],[" or, ",y-5=7(x-4)],[" or, "quad,y-5=7x-28],[:.quad,7x-y-23=0" is the required equation. "]:} \begin{array}{ll}
& y-y_{1}=m\left(x-x_{1}\right) \\
\text { or, } & y-5=7(x-4) \\
\text { or, } \quad & y-5=7 x-28 \\
\therefore \quad & 7 x-y-23=0 \text { is the required equation. }
\end{array} y − y 1 = m ( x − x 1 ) or, y − 5 = 7 ( x − 4 ) or, y − 5 = 7 x − 28 ∴ 7 x − y − 23 = 0 is the required equation.
(a) Find the equation of line passing through
(
2
,
−
3
)
(
2
,
−
3
)
(2,-3) (2,-3) ( 2 , − 3 ) and inclined at an angle of
135
∘
135
∘
135^(@) 135^{\circ} 135 ∘ with the positive direction of
X
X
X \mathrm{X} X -axis.
⇒
⇒
=>quad \Rightarrow \quad ⇒ Here, passing point
(
x
1
,
y
1
)
=
(
2
,
−
3
)
x
1
,
y
1
=
(
2
,
−
3
)
(x_(1),y_(1))=(2,-3) \left(\mathrm{x}_{1}, \mathrm{y}_{1}\right)=(2,-3) ( x 1 , y 1 ) = ( 2 , − 3 )
Inclination with
+
v
e
x
+
v
e
x
+vex +\mathrm{ve} x + v e x -axis
(
θ
)
=
135
∘
(
θ
)
=
135
∘
(theta)=135^(@) (\theta)=135^{\circ} ( θ ) = 135 ∘
∴
∴
:.quad \therefore \quad ∴ slope
(
m
)
=
tan
θ
=
tan
135
∘
=
−
1
(
m
)
=
tan
θ
=
tan
135
∘
=
−
1
(m)=tan theta=tan 135^(@)=-1 (\mathrm{m})=\tan \theta=\tan 135^{\circ}=-1 ( m ) = tan θ = tan 135 ∘ = − 1
We know that,
Equation of straight line passing through
(
x
1
,
y
1
)
x
1
,
y
1
(x_(1),y_(1)) \left(\mathrm{x}_{1}, \mathrm{y}_{1}\right) ( x 1 , y 1 ) and having slope
m
m
m \mathrm{m} m is;
y
−
y
1
=
m
(
x
−
x
1
)
y
−
y
1
=
m
x
−
x
1
y-y_(1)=m(x-x_(1)) \mathrm{y}-\mathrm{y}_{1}=\mathrm{m}\left(\mathrm{x}-\mathrm{x}_{1}\right) y − y 1 = m ( x − x 1 )
or,
y
−
(
−
3
)
=
−
1
(
x
−
2
)
y
−
(
−
3
)
=
−
1
(
x
−
2
)
quad y-(-3)=-1(x-2) \quad y-(-3)=-1(x-2) y − ( − 3 ) = − 1 ( x − 2 )
or,
y
+
3
=
−
x
+
2
y
+
3
=
−
x
+
2
quad y+3=-x+2 \quad y+3=-x+2 y + 3 = − x + 2
∴
x
+
y
+
1
=
0
∴
x
+
y
+
1
=
0
:.quadx+y+1=0 \therefore \quad \mathrm{x}+\mathrm{y}+1=0 ∴ x + y + 1 = 0 is the required equation. (b)
Find the equation of line passing through
(
5
,
7
)
(
5
,
7
)
(5,7) (5,7) ( 5 , 7 ) and inclined at an angle of
45
∘
45
∘
45^(@) 45^{\circ} 45 ∘ with the positive direction of
X
X
X \mathrm{X} X -axis.
⇒
⇒
=>quad \Rightarrow \quad ⇒ Here, passing point
(
x
1
,
y
1
)
=
(
5
,
7
)
x
1
,
y
1
=
(
5
,
7
)
(x_(1),y_(1))=(5,7) \left(\mathrm{x}_{1}, \mathrm{y}_{1}\right)=(5,7) ( x 1 , y 1 ) = ( 5 , 7 )
Inclination with +ve
x
x
x \mathrm{x} x -axis
(
θ
)
=
45
∘
(
θ
)
=
45
∘
(theta)=45^(@) (\theta)=45^{\circ} ( θ ) = 45 ∘
∴
∴
:.quad \therefore \quad ∴ slope
(
m
)
=
tan
θ
=
tan
45
∘
=
1
(
m
)
=
tan
θ
=
tan
45
∘
=
1
(m)=tan theta=tan 45^(@)=1 (\mathrm{m})=\tan \theta=\tan 45^{\circ}=1 ( m ) = tan θ = tan 45 ∘ = 1
We know that,
Equation of straight line passing through
(
x
1
,
y
1
)
x
1
,
y
1
(x_(1),y_(1)) \left(\mathrm{x}_{1}, \mathrm{y}_{1}\right) ( x 1 , y 1 ) and having slope
m
m
m \mathrm{m} m is;
y
−
y
1
=
m
(
x
−
x
1
)
or,
y
−
7
=
1
(
x
−
5
)
or,
y
−
7
=
x
−
5
∴
x
−
y
+
2
=
0
is the required equation.
y
−
y
1
=
m
x
−
x
1
or,
y
−
7
=
1
(
x
−
5
)
or,
y
−
7
=
x
−
5
∴
x
−
y
+
2
=
0
is the required equation.
{:[,y-y_(1)=m(x-x_(1))],[" or, "quad,y-7=1(x-5)],[" or, "quad,y-7=x-5],[:.quad,x-y+2=0" is the required equation. "]:} \begin{array}{ll}
& y-y_{1}=m\left(x-x_{1}\right) \\
\text { or, } \quad & y-7=1(x-5) \\
\text { or, } \quad & y-7=x-5 \\
\therefore \quad & x-y+2=0 \text { is the required equation. }
\end{array} y − y 1 = m ( x − x 1 ) or, y − 7 = 1 ( x − 5 ) or, y − 7 = x − 5 ∴ x − y + 2 = 0 is the required equation.
(c) Find the equation of line passing through
(
2
,
2
3
)
(
2
,
2
3
)
(2,2sqrt3) (2,2 \sqrt{3}) ( 2 , 2 3 ) and inclined at angle of
30
∘
30
∘
30^(@) 30^{\circ} 30 ∘ with the positive direction of
X
X
X \mathrm{X} X -axis.
⇒
⇒
=>quad \Rightarrow \quad ⇒ Here, passing point
(
x
1
,
y
1
)
=
(
2
,
2
3
)
x
1
,
y
1
=
(
2
,
2
3
)
(x_(1),y_(1))=(2,2sqrt3) \left(\mathrm{x}_{1}, \mathrm{y}_{1}\right)=(2,2 \sqrt{3}) ( x 1 , y 1 ) = ( 2 , 2 3 )
Inclination with +ve
x
x
x \mathrm{x} x -axis
(
θ
)
=
30
∘
(
θ
)
=
30
∘
(theta)=30^(@) (\theta)=30^{\circ} ( θ ) = 30 ∘
∴
∴
:.quad \therefore \quad ∴ slope
(
m
)
=
tan
θ
=
tan
30
∘
=
1
3
(
m
)
=
tan
θ
=
tan
30
∘
=
1
3
(m)=tan theta=tan 30^(@)=(1)/(sqrt3) (\mathrm{m})=\tan \theta=\tan 30^{\circ}=\frac{1}{\sqrt{3}} ( m ) = tan θ = tan 30 ∘ = 1 3
We know that,
Equation of straight line passing through
(
x
1
,
y
1
)
x
1
,
y
1
(x_(1),y_(1)) \left(\mathrm{x}_{1}, \mathrm{y}_{1}\right) ( x 1 , y 1 ) and having slope
m
m
m \mathrm{m} m is;
y
−
y
1
=
m
(
x
−
x
1
)
y
−
y
1
=
m
x
−
x
1
y-y_(1)=m(x-x_(1)) \mathrm{y}-\mathrm{y}_{1}=\mathrm{m}\left(\mathrm{x}-\mathrm{x}_{1}\right) y − y 1 = m ( x − x 1 )
or,
y
−
2
3
=
1
3
(
x
−
2
)
y
−
2
3
=
1
3
(
x
−
2
)
quad y-2sqrt3=(1)/(sqrt3)(x-2) \quad y-2 \sqrt{3}=\frac{1}{\sqrt{3}}(x-2) y − 2 3 = 1 3 ( x − 2 )
or,
3
y
−
2
×
3
=
x
−
2
3
y
−
2
×
3
=
x
−
2
quadsqrt3y-2xx3=x-2 \quad \sqrt{3} \mathrm{y}-2 \times 3=\mathrm{x}-2 3 y − 2 × 3 = x − 2
∴
x
−
3
y
+
4
=
0
∴
x
−
3
y
+
4
=
0
:.quad x-sqrt3y+4=0 \therefore \quad x-\sqrt{3} y+4=0 ∴ x − 3 y + 4 = 0 is the required equation.
(d) Find the equation of the line passing through the point
(
1
,
2
)
(
1
,
2
)
(1,2) (1,2) ( 1 , 2 ) and making an angle of
tan
−
1
(
1
3
)
tan
−
1
1
3
tan^(-1)((1)/(3)) \tan ^{-1}\left(\frac{1}{3}\right) tan − 1 ( 1 3 ) with the
X
X
X \mathrm{X} X -axis.
⇒
⇒
=>quad \Rightarrow \quad ⇒ Here, passing point
(
x
1
,
y
1
)
=
(
1
,
2
)
x
1
,
y
1
=
(
1
,
2
)
(x_(1),y_(1))=(1,2) \left(\mathrm{x}_{1}, \mathrm{y}_{1}\right)=(1,2) ( x 1 , y 1 ) = ( 1 , 2 )
Inclination with
+
v
e
x
+
v
e
x
+vex +\mathrm{ve} x + v e x -axis
(
θ
)
=
tan
−
1
(
1
3
)
(
θ
)
=
tan
−
1
1
3
(theta)=tan^(-1)((1)/(3)) (\theta)=\tan ^{-1}\left(\frac{1}{3}\right) ( θ ) = tan − 1 ( 1 3 )
or,
tan
θ
=
1
3
tan
θ
=
1
3
quad tan theta=(1)/(3) \quad \tan \theta=\frac{1}{3} tan θ = 1 3
∴
∴
:.quad \therefore \quad ∴ slope
(
m
)
=
1
3
(
m
)
=
1
3
(m)=(1)/(3) (\mathrm{m})=\frac{1}{3} ( m ) = 1 3
We know that,
Equation of straight line passing through
(
x
1
,
y
1
)
x
1
,
y
1
(x_(1),y_(1)) \left(\mathrm{x}_{1}, \mathrm{y}_{1}\right) ( x 1 , y 1 ) and having slope
m
m
m \mathrm{m} m is;
y
−
y
1
=
m
(
x
−
x
1
)
y
−
y
1
=
m
x
−
x
1
y-y_(1)=m(x-x_(1)) y-y_{1}=m\left(x-x_{1}\right) y − y 1 = m ( x − x 1 )
or,
y
−
2
=
1
3
(
x
−
1
)
y
−
2
=
1
3
(
x
−
1
)
quad y-2=(1)/(3)(x-1) \quad y-2=\frac{1}{3}(x-1) y − 2 = 1 3 ( x − 1 )
or,
3
y
−
6
=
x
−
1
3
y
−
6
=
x
−
1
quad3y-6=x-1 \quad 3 y-6=x-1 3 y − 6 = x − 1
∴
x
−
3
y
+
5
=
0
∴
x
−
3
y
+
5
=
0
:.quadx-3y+5=0 \therefore \quad \mathrm{x}-3 \mathrm{y}+5=0 ∴ x − 3 y + 5 = 0 is the required equation.
No comments:
Post a Comment